Crosstalk among m6A RNA methylation, hypoxia and metabolic reprogramming in TME: from immunosuppressive microenvironment to clinical application - Fusheng Zhang; Haiyang Liu; Meiqi Duan; Guang Wang; Zhenghou Zhang; Yutian Wang; Yiping Qian; Zhi Yang; Xiaofeng Jiang (Journal of Hematology & Oncology, 2022)
Abstract The tumor microenvironment (TME), which is regulated by intrinsic oncogenic mechanisms and epigenetic modifications, has become a research hotspot in recent years. Characteristic features of TME include hypoxia, metabolic dysregulation, and immunosuppression. One of the most common RNA modifications, N6-methyladenosine (m6A) methylation, is widely involved in the regulation of physiological and pathological processes, including tumor development. Compelling evidence indicates that m6A methylation regulates transcription and protein expression through shearing, export, translation, and processing, thereby participating in the dynamic evolution of TME. Specifically, m6A methylation-mediated adaptation to hypoxia, metabolic dysregulation, and phenotypic shift of immune cells synergistically promote the formation of an immunosuppressive TME that supports tumor proliferation and metastasis. In this review, we have focused on the involvement of m6A methylation in the dynamic evolution of tumor-adaptive TME and described the detailed mechanisms linking m6A methylation to change in tumor cell biological functions. In view of the collective data, we advocate treating TME as a complete ecosystem in which components crosstalk with each other to synergistically achieve tumor adaptive changes. Finally, we describe the potential utility of m6A methylation-targeted therapies and tumor immunotherapy in clinical applications and the challenges faced, with the aim of advancing m6A methylation research.